اسلام میں سزاؤں کا تصور:جدید اور روایتی تفسیری لٹریچر کا تجزیاتی مطالعہThe Concept of Punishments in Islam: An Analytical Study of Modern and Traditional Interpretive Literature (Al-Qamar, 2024)
This article examines the concept of “Islamic Punishments” by analyzing both “Traditional and Modern Interpretive Literature”. It explores two primary schools of thought: the traditional school, based on classical interpretations of the “Quran and Sunnah”, and the modern school, which incorporates progressive views and human rights considerations. The traditional exegetical literature, including works like Ma'ariful Quran by Mufti Muhammad Shafi Usmani and Tafheem-ul-Quran by Maulana Syed Maududi, emphasizes the connection between punishments, social order, and divine will, advocating that punishments are necessary not only for individual reform but also for fulfilling Allah’s rights and maintaining societal discipline. In contrast, modern exegetical works, such as Matalib-ul-Furqan by Ghulam Ahmed Pervez, Tafseer-ul-Quran by Sir Syed Ahmad Khan, Al-Bayan by Javed Ahmad Ghamidi, and Tadabbur-e-Quran by Ameen Ahsan Islahi, present a more flexible approach, asserting that punishments should be adapted to contemporary circumstances and focused on human welfare, individual rights, and social justice. This paper aims to provide a comparative analysis of these perspectives, shedding light on the evolving interpretations of Islamic punishments in the context of changing social and legal norms. The importance of this study lies in its contribution to the ongoing discourse on the relevance of Islamic legal principles in modern society, offering insights into how these traditional concepts can be understood and applied in the contemporary world.